THE INFLUENCE CIVICS TEACHER AND LEARNING ATMOSPHERE TOWARDS DISCIPLINE DEVELOPMENT OF STUDENTS IN JUNIOR HIGH SCHOOL KARAWANG) - Sapriya, Yogi Nugraha (Department of Civic Education, 2015)
This study reviews (1) Influence Civics teacher performance to the development of the discipline of students, (2) Influence of learning atmosphere on the development of the discipline of learners, and (3) Influence of Civics teacher performance and learning atmosphere for the development of the discipline of students. The research uses a quantitative approach with survey method. Data collection using the study questionnaire. The population are class VIII. The number of schools included in the sample amounted to 6 schools. Number of students of class VIII which is composed of as many as 2.368 school sixth respondent. Retrieval technique with multistage random sampling then taken 10% of the total population of each school grade VIII, thus totaling 236 respondents at 95% level of truth. The results showed that (1) Performance Civics teacher influence the development of the discipline of students, (2) learning atmosphere influence the development of the discipline of students, and (3) Performance Civics teachers and learning climate simultaneously influence the development of the discipline of students.Keyword: Civics Teacher Performance, Learning Atmosphere, Development of Discipline of Students Attitudes